2011
DOI: 10.3109/09638288.2010.515701
|View full text |Cite
|
Sign up to set email alerts
|

Dual tasking and stuttering: from the laboratory to the clinic

Abstract: Dual tasking during treatment using the DAS-D appears to be a viable clinical procedure. Further research is required to establish effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…In these studies, while the primary task (speech) is in the verbal domain, the secondary tasks are in a different domain, such as spatial and mental arithmetic tasks. However, increases (Bosshardt, 2002;Metten et al, 2011) or no change (Bosshardt et al, 2002;Kamhi & McOsker, 1982) in the stuttering rate are also reported in comparison to single-task performances. Reasons for the discrepancy may include differences in the relative difficulty (e.g., too simple secondary movement task in Kamhi & McOsker, 1982; too demanding Stroop test in Caruso et al, 1994) and degrees of interference between the two tasks (both tasks in the same verbal domain; Bosshardt et al, 2002;Metten et al, 2011), as "the speechproduction system of PWS makes it more vulnerable to interference from concurrent attention-demanding" tasks.…”
Section: Wm In Pwsmentioning
confidence: 92%
See 2 more Smart Citations
“…In these studies, while the primary task (speech) is in the verbal domain, the secondary tasks are in a different domain, such as spatial and mental arithmetic tasks. However, increases (Bosshardt, 2002;Metten et al, 2011) or no change (Bosshardt et al, 2002;Kamhi & McOsker, 1982) in the stuttering rate are also reported in comparison to single-task performances. Reasons for the discrepancy may include differences in the relative difficulty (e.g., too simple secondary movement task in Kamhi & McOsker, 1982; too demanding Stroop test in Caruso et al, 1994) and degrees of interference between the two tasks (both tasks in the same verbal domain; Bosshardt et al, 2002;Metten et al, 2011), as "the speechproduction system of PWS makes it more vulnerable to interference from concurrent attention-demanding" tasks.…”
Section: Wm In Pwsmentioning
confidence: 92%
“…Various experimental paradigms have been used to measure WM abilities of PWS, such as rhyme judgment, letter recall, and phoneme monitoring (Bosshardt et al, 2002;Jones et al, 2012;Sasisekaran & Basu, 2017). In particular, nonword repetition task and dual task have been repeatedly employed in previous studies (Anderson & Wagovich, 2010;Anderson et al, 2006;Arends et al, 1988;Bosshardt, 1993Bosshardt, , 1999Bosshardt, , 2002Bosshardt et al, 2002;Byrd et al, 2015Byrd et al, , 2012Eichorn et al, 2016Eichorn et al, , 2019Hakim & Bernstein Ratner, 2004;Kamhi & McOsker, 1982;Metten et al, 2011;Sasisekaran, 2013;Vasić & Wijnen, 2005).…”
Section: Wm In Pwsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of cognitive resources during communication has also been shown to have an effect on stuttering (see Metten et al, 2011). Metten et al (2011) found that stuttering increased when a competing linguistic task diverted cognitive resources away from speaking.…”
Section: Modulating Factorsmentioning
confidence: 96%
“…Metten et al (2011) found that stuttering increased when a competing linguistic task diverted cognitive resources away from speaking. Interestingly, dual tasking also interfered with speech production for the normally fluent participants in the control group, who had many more normal disfluencies in this condition.…”
Section: Modulating Factorsmentioning
confidence: 98%